A Decadal Trend Analysis of Land Use Changes (1980 – 2020) in the Calabar River Basin, Southern Nigeria - Temple Abali; Leonard Onyinyechi Michael Aminigbo (International Journal of Information Systems and Informatics, 2021)
The necessity for a platform for diverse geo-spatial investigations in the study area prompted this study. Using a Geographic Information System (GIS) analysis, the study looked at land use trends over a 30-year period (1980-2010). Urban and farm land use types encroached on grassland, forest, bareland, and waterbody by 17.54 percent and 13.59 percent, respectively, with losses in grassland, forest, bareland, and water bodies of 12.01 percent, 11.01 percent, 4.62 percent, and 3.5 percent. As a result, maps/charts of land use changes in the study area have been created, revealing a rapidly deforested region for urbanization and agricultural operations. This result will offer planners and decision-makers with a quick assessment of the possible impact of human activities in the study region, as well as the commencement of relevant efforts to reduce the impact. Furthermore, because it has provided accurate information related to land use changes over time, it will yield valuable information for the analysis of the environmental impacts of population pressure, agriculture, urban expansion, resettlement program, climate change, resources managers, development agents, fund providers, socio-economic development planners, public administrators, and environmentalists.